Penguatan Nilai-Nilai Keberagaman dan Kebhinekaan Berbasis Komunikasi Antar Agama di Desa Wonorejo Situbondo - Ainiyah, Nur; Mufaridah, Hanik (Proceedings of Annual Conference on Community Engagement, 2022)
This empowerment aims to show how to strengthen the values of diversity and diversity based on interfaith communication which is manifested in the national village community in Wonorejo, Situbondo district. So the focus of assistance is the development of the values of diversity and diversity through inter-religious communication that is intertwined in daily life, so that it can be in line with concern for local cultural values and religious tolerance. The formulation of the problem is: 1) What are the steps for mentoring and empowering the values of diversity and diversity in group-based village communities? and 2) How to strengthen the values of diversity and diversity based on inter-religious communication so as to create independence of religious tolerance? With a theoretical framework, communication between religions and diversity will provide a complete picture regarding the focus of the mentoring program. With the interfaith communication approach method based on the Participatory Rural Appraisal approach, it involves the community and stakeholders in problem solving. Furthermore, the mentoring steps are providing understanding regarding the focus of assistance, taking action, implementing programs, and strengthening the values of diversity and diversity through group communication channels. Then, carry out evaluations related to the program, as well as study the obstacles and progress during the program. The results of this mentoring and empowerment activity are creating awareness of diversity and diversity to maintain religious tolerance on the basis of women's groups and organizations in Wonorejo. In addition, it creates a strengthening of understanding of diversity and diversity through inter-religious communication by religious leaders and religious adherents, so that an independent institution is created that becomes a mediator in solving religious problems at the village level.